A test of dividend irrelevance using volume reactions to a change in dividend policy - Richardson, Gordon; Sefcik, Stephan E.; Thompson, Rex (Journal of Financial Economics, 1986)
We investigate the implication of clientele theories that changes in dividend policy should result in a marked increase in trading volume as shareholder clienteles change. With 192 firms announcing their first cash dividend we document both an increase in trading volume and firm value around the announcement date. We integrate these results to distinguish between the volume response to good news about the future and clientele adjustments to a change in dividend policy. Our results suggest that volume increases primarily in response to the signal about future earnings contained in the dividend. Clientele adjustments are small.